Mempertahankan Keunggulan melalui Sumber Daya: Strategi Kepemimpinan Biaya Usaha Mikro di Tengah Lonjakan Harga Input - Adha, Ishbir Mujahid; Rini, Endang Sulistya; Absah, Yeni (Badung Bali: Politeknik Negeri Bali, 2024)
Resource Advantage idea in business competitiveness promotes the development of competitive advantages by enterprises through their better possession of resources. MSME need to retain and improve their competitive advantage through cost leadership strategy. To achieve the competitiveness, MSME have to pay attention to their resource advantage. In terms of cost leadership, MSMEs must also assess the quality and superiority of their available resources. Resource superiority is a significant concern when it comes to competition based on low prices. This study aims to investigate the tactics employed by micro enterprises in addressing sudden increases in the costs of production inputs in order to preserve their competitive edge. The study utilised a sample of organisations who successfully maintained company continuity following instances of price surge since 2022. There were a total of 30 businesses that took part in this research. The chosen methodology is a qualitative approach that involves conducting content analysis on the interview results. Typically, corporations choose raising the prices of their products as the input is rising. MSME is prefer to raise the price while retaining the quality rather than lower the quality to keep the price in check.